CS-PAT Climate Services – Participatory Assessment Tool - Giraldo, Diana; Grossi, Amanda; Ghosh, Aniruddha; Sagliocco, Livia; Gamoyo, Majambo; Ahmed, Jemal; Koech, Grace; Ramirez Villegas, Julian (2025)
CS-PAT (Climate Services – Participatory Assessment Tool) is a structured, participatory framework designed to assess the readiness, performance, and investment needs of national climate service systems. By combining standardized indicators with stakeholder-led diagnostics, CS-PAT identifies institutional strengths, gaps, and bottlenecks across the climate services value chain. The tool translates assessment results into actionable investment pathways, enabling governments, development partners, and service providers to prioritize reforms, strengthen delivery models, and scale climate services with measurable impact. Built for comparability, learning, and repeat application over time, CS-PAT supports evidence-based decision-making for resilient and inclusive climate service systems. This brief includes Annex I, which provides a sample interview protocol structured around the ten CS-PAT diagnostic dimensions, serving as a practical guide for standardized, participatory qualitative assessment across diverse stakeholder groups.